2017
DOI: 10.1038/ismej.2017.145
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a primate origin of zoonotic Helicobacter suis colonizing domesticated pigs

Abstract: Helicobacter suis is the second most prevalent Helicobacter species in the stomach of humans suffering from gastric disease. This bacterium mainly inhabits the stomach of domesticated pigs, in which it causes gastric disease, but it appears to be absent in wild boars. Interestingly, it also colonizes the stomach of asymptomatic rhesus and cynomolgus monkeys. The origin of modern human-, pig- or non-human primate-associated H. suis strains in these respective host populations was hitherto unknown. Here we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…410 kya. Coevolution between a microbe and its host generally results in decreased pathogenicity, but a disruption caused by jumps between hosts has been associated with an increase in disease severity, as shown for Staphylococcus aureus and recently also for H. suis [54,55]. Since infection with H. cetorum has been correlated with gastric ulcers in marine mammals [13,17], these animals are thus probably not the natural host.…”
Section: Discussionmentioning
confidence: 99%
“…410 kya. Coevolution between a microbe and its host generally results in decreased pathogenicity, but a disruption caused by jumps between hosts has been associated with an increase in disease severity, as shown for Staphylococcus aureus and recently also for H. suis [54,55]. Since infection with H. cetorum has been correlated with gastric ulcers in marine mammals [13,17], these animals are thus probably not the natural host.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in infection rates could come from the meat consumption patterns in Japan, as people in Tohoku and Kyushu regions were reported to eat more pork than beef compared to other regions. Pigs have already been confirmed to be a reservoir of Hs 27 . We were unable to obtain the infection rate in the general population in this study.…”
Section: Discussionmentioning
confidence: 73%
“…A mixed infection with H. pylori and H. suis was present in one patient. MLST analysis showed that the strains of both H. suis‐ positive patients belonged to the porcine‐associated sequence types 1 and 4 …”
Section: Resultsmentioning
confidence: 99%
“…As H. suis naturally colonizes the stomach of pigs and non‐human primates, while H. heilmannii and H. ailurogastricus are mainly associated with dogs and cats, these animals might function as a reservoir for human infections. MLST analysis demonstrated that the H. suis strains from both patients were porcine associated . The exact route of transmission from animals to humans is not yet clear.…”
Section: Discussionmentioning
confidence: 99%